Quantitative analysis on the correlation between risks: empirical evidence from banks in United Kingdom - Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Organisation of Scientific Research (IOSR), 2013)
Financial institutions or banks are faced with several types of risks that are uniquely related to the nature of the industry. Therefore it is a must for banks to have risk mitigation methods in order to maintain its competitiveness and sustainability. For the purpose of this paper, four unique risks related to the banking industry will be discussed, as well as to provide empirical study on the relationship between these risks. These risks are liquidity risk, operational risk, credit risk and market risk. The focus of this study is on ten listed banks in United Kingdom with complete secondary data from the year 2002 to 2011. Liquidity risk is measured by the ratio of total loans to total deposits, operational risk is calculated based on two ratios, i.e. the ratio of operating expenses to total assets and the ratio of non-performing loans to total loans. Credit risk is based on the probability of default based on Altman’s z score equation and market risk is calculated based on the standard deviation of quarterly stock returns. The findings show the evidence that there is a relationship between tested risk and it is expected that the findings will be the interest of the bankers to see which risk is the source of other risks.